Upaya peningkatan pengetahuan dan pencegahan demam berdarah pada masyarakat kelurahan darma - Amin, Hadriyani; Safitri, Rusni (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Dengue hemorrhagic fever or abbreviated as DHF is an acute febrile disease caused by the dengue virus. This virus enters the human bloodstream through the bite of mosquitoes from the Aedes genus, for example Aedes aegypti or Aedes albopictus. This disease is characterized by high fever continuously for 2 to 7 days and is accompanied by bleeding and shock which, if not treated immediately, can cause death Objective: The aim of this Community Service is to increase public knowledge about dengue fever and its prevention in Darma Environmental Batu-batu Village. Method: Knowledge increasing activities regarding increasing knowledge and preventing dengue fever were carried out. On Thursday, May 27 2024, 10.00 WITA, the opening of community service activities with the theme "Increasing Knowledge and Prevention of Dengue Fever" took place in the Darma Environmental Batu-batu sub-district. The media used is material in the form of leaflets and posters. The implementation of community service uses the community outreach method, namely involving the community and students during the implementation process. Result: From the results of the pre-test analysis, most of the community does not know about dengue fever and its prevention, but after counseling, the post-test results show that almost all people understand about dengue fever and its prevention. Conclusion: From the community service activities that have been carried out in the Darma Environmental Batu-Batu Subdistrict by the STIKES Bina Generasi Polewali Mandar community service team, it can be concluded that public knowledge regarding dengue hemorrhagic fever (DBD) needs to continue to be improved continuously, climate change, especially in the rainy season very vulnerable to the spread of dengue fever so it is necessary to empower the community in preventing dengue fever, one of which is through 3M and PSN